Boundaries of the mind the individual in the fragile sciences : cognition - Wilson, Robert A. (Cambridge University Press, 2004)
Where does the mind begin and end? Most philosophers and cognitive scientists take the view that the mind is bounded by the skull or skin of the individual. Robert Wilson, in this provocative and challenging 2004 book, provides the foundations for the view that the mind extends beyond the boundary of the individual. The approach adopted offers a unique blend of traditional philosophical analysis, cognitive science, and the history of psychology and the human sciences. A forthcoming companion volume Genes and the Agents of Life will explore the theme in the biological sciences. Written with verve and clarity, this ambitious book will appeal to a broad swathe of professionals and students in philosophy, psychology, cognitive science, and the history of the behavioural and human sciences.